The importance of physical activity for the development of motor skills of younger school age children - Bukvić, Zorana; Nikolić, Dejan; Ćirović, Dragana (Medicinski podmladak, 2021)
Physical activity has a very important role in the motor and psychological development of in pediatric population. The maturation of human motor abilities takes place gradually. It depends on several factors, including but not limited to: individual differences, health condition, quality of neuromuscular structures and stimulating factors.This review point to a fact that a child who has developed a high level of motor skills will be physically active and positively accepted by peers, while a clumsy child usually struggle to catch peers in physical activities thus eagerly observes them. This has a negative impact on the motor competencies, as well as on the child's self-confidence, general mood, relationships with family and friends, and success in a school.In younger school age children, physical exercise has a great influence on the upbringing and complete development of the child's personality, so it is very important to encourage children to be as physically active as possible during this period.Key words:
Keywords: physical activity, children, younger school age, motor skills, children’s development.